2019
DOI: 10.1371/journal.pone.0214040
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, salivary cortisol and atopic diseases in young children

Abstract: Background Children with atopic disease may have reduced health-related quality of life (QoL) and morning cortisol. Possible links between QoL, morning cortisol and atopic disease are unclear. We aimed to determine if QoL was associated with morning salivary cortisol at two years of age, and if asthma, atopic dermatitis and/or allergic sensitisation influenced this association. Secondarily, we aimed to determine if QoL at one year of age was associated with salivary cortisol one year later. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another goal of this study was to examine sex as a biological variable in the prenatal programming of allergic immune function by stress hormone. Epidemiological studies examining the effect of maternal stress on atopic disease in offspring have conflicting results (12,20,(37)(38)(39)(40)(41)(42). Lee et al (38) examined 765 mother-child dyads and found an association between prenatal stress and asthma risk in 6 year old boys, while postnatal stress was associated with asthma in 6 years old girls, tendencies that were also observed in another cohort study of Mexican children by Rosa et al (39), Lee et al (38).…”
Section: Discussionmentioning
confidence: 98%
“…Another goal of this study was to examine sex as a biological variable in the prenatal programming of allergic immune function by stress hormone. Epidemiological studies examining the effect of maternal stress on atopic disease in offspring have conflicting results (12,20,(37)(38)(39)(40)(41)(42). Lee et al (38) examined 765 mother-child dyads and found an association between prenatal stress and asthma risk in 6 year old boys, while postnatal stress was associated with asthma in 6 years old girls, tendencies that were also observed in another cohort study of Mexican children by Rosa et al (39), Lee et al (38).…”
Section: Discussionmentioning
confidence: 98%
“…Chronic downregulation of HPA axis activity and a disrupted pattern of diurnal cortisol variation may therefore place individuals at higher risk for inflammatory diseases such as asthma (Buske-Kirschbaum, 2009;Chrousos, 1995). Disturbances in HPA axis functioning have been described in children with asthma and related allergic disorders, suggesting a role of HPA axis in the early development of repeated wheeze and later asthma, although results have been largely crosssectional and mixed (Buske-Kirschbaum et al, 2003;Dreger, Kozyrskyj, HayGlass, Becker, & MacNeil, 2010;Rolfsjord et al, 2019;Stenius et al, 2011). While some studies have found lower basal salivary cortisol, a blunted diurnal rhythm, and reduced reactivity to stressors in those with a family history of asthma or asthma diagnosis (Bakkeheim, Mowinckel, Carlsen, Burney, & Lødrup Carlsen, 2010;Ball, Anderson, Minto, & Halonen, 2006;Wamboldt, Laudenslager, Wamboldt, Kelsay, & Hewitt, 2003), others fail to support an association between dysregulated cortisol and asthma or wheeze (Vink, Boezen, Postma, & Rosmalen, 2013;Wolf, Nicholls, & Chen, 2008).…”
mentioning
confidence: 99%